2011
DOI: 10.1590/s0004-27492011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Literature systematic review on the ophthalmological side effects of interferons

Abstract: Interferons alpha and beta have been used worldwide for a few decades, altering the natural history of several severe diseases including hepatitis C, cancer and immu nemediated conditions such as multiple sclerosis. The adverse events profile of interferons is well established, but only isolated reports of ophthalmological compli ca tions of interferon therapy have been published. The objective of this study was to carry out a literature systematic review on the subject, bringing to light the need for ca reful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…This is thought to increase leukocyte adhesion, which may trigger microcirculation obstruction (1)(2)(3) . Furthermore, it has been reported that IFN induces thrombogenic antibody proliferation (9) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is thought to increase leukocyte adhesion, which may trigger microcirculation obstruction (1)(2)(3) . Furthermore, it has been reported that IFN induces thrombogenic antibody proliferation (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Typical ocular complications associated with its use include ischemic retinopathy associated with cotton wool spots, retinal hemorrhages, and peripheral vascular obstructions (7,9) . Microaneurysms, neovascular glaucomas, and ischemic optic neuropathies have also been observed (2,7,8) . Currently, IFN is the only accepted adjuvant treatment for patients with high-risk relapse melanoma (1) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations